Appointment waiting times and education level influence the quality of bowel preparation in adult patients undergoing colonoscopy - Chan, W.K.; Saravanan, A.; Manikam, J.; Goh, K.L.; Mahadeva, S. (2011)
BACKGROUND: Risk factors for poor bowel preparation are recognized to be independent of the type of bowel preparation method used. Patient and administrative factors influencing bowel preparation are known to vary in different healthcare systems.